Disparity Evaluation Loss State Finance in Decision Court Action Criminal Corruption: A Study of Consistency and Rationality Juridical - Ronald Hasudungan Sianturi (Universitas Medan Area, 2026)
This study examines the disparity in the evaluation of state financial losses in corruption court decisions in Indonesia, with a particular focus on juridical consistency and rationality in judicial application. The phenomenon of disparity in judges’ decisions in determining the amount of state financial losses has become a serious issue related to legal certainty, justice, and the effectiveness of criminal law enforcement in corruption cases. This research employs a normative juridical method with comparative case, conceptual, and statutory approaches. The analysis was conducted on a number of corruption court decisions at various judicial levels, ranging from the District Court, High Court, to the Supreme Court. The results of the study indicate that disparities in the assessment of state financial losses arise from three main factors, namely the non-uniformity of audit methodologies among state financial auditing institutions, the absence of measurable and structured standards of proof regarding the components of state losses, and inconsistencies in the acceptance and consideration of expert testimony in court proceedings. Therefore, this research recommends the formulation of judicial guidelines and the unification of standard methodologies for the quantification of state financial losses as instruments to strengthen juridical consistency, judicial accountability, and fairness in corruption adjudication in Indonesia.